The effect of job demands and work-life balance on turnover intention: The mediating role of burnout - Faradila Lutfia Firhani; Justine Tanuwijaya; B Medina Nilasari (Universitas Nusa Cendana, 2026)
Employee turnover intention remains a critical challenge in the banking industry, particularly in organizations facing heightened work demands and performance pressures. This study investigates the effects of job demands and work–life balance on turnover intention, while examining the mediating role of burnout among banking employees in Indonesia. Drawing on the Job Demands–Resources (JD–R) framework, a quantitative research design was employed using purposive sampling to collect data from 178 employees. Structural Equation Modeling (SEM) using AMOS was applied to examine the proposed relationships among the constructs. The findings reveal that job demands positively and significantly influence burnout, indicating that excessive work-related pressures contribute to employee psychological exhaustion. However, job demands do not directly affect turnover intention. Likewise, work–life balance does not significantly influence burnout or turnover intention. Contrary to expectations, burnout does not significantly predict turnover intention and fails to mediate the relationships between job demands, work–life balance, and turnover intention. These findings suggest that turnover intention among banking employees may be shaped by factors beyond job-related stressors and personal resource management, highlighting the importance of considering organizational and contextual determinants in employee retention strategies. The study contributes to the turnover intention literature by providing empirical evidence that challenges the assumed mediating role of burnout within high-pressure banking environments and offers practical insights for human resource policies aimed at improving employee retention. Keywords: Job Demands; Work Life Balance; Burnout; Turnover; Intention; Banking